Identity crisis how identification is overused and misunderstood - Harper, Jim (Cato Institute, 2006)
Showing an ID doesn't protect against terrorism the way people think. This book explodes the myths surrounding identification and, at the same time, shows the way forward.
Keywords: Privacy, Right of : United States; Identification : United States